Relationship between psychosocial problems and satisfaction with GP communication in German primary care practices: a structural equation model based on the cross-sectional GPCare-1 patient study - Birgitta Weltermann; Thomas Welchowski; Boris Gavrilov; Carmen Hunzelar; Florian Bockheim; Joana Paños-Willuhn; Luisa Offenberg; Maja Oberholz; Nur Ikar; Juliane Sachschal (BMJ Open)
Objectives This study examined the relationship between primary care patients’ psychosocial problems, other patient characteristics that are associated with satisfaction with overall care and satisfaction with general practitioner (GP) communication.Design A cross-sectional survey was conducted. Patients filled an anonymous two-page questionnaire on various socio-demographic, medical characteristics and their satisfaction with GP communication. Structural equation modelling evaluated associations of various patient characteristics, including psychosocial problems with GP communication.Setting General practices in Germany.Participants A total of 813 patients from 12 GP practices participated. The survey was conducted in summer 2020 during a COVID-19 lockdown.Results The estimated response rate was 24.1%. The prevalence of psychosocial problems in the sample was 30%. The three most frequent problems were excessive stress at work (19%), financial problems/debts (9%) and loneliness (8%). Most patients agreed that their GP takes their problems seriously (71%), feeling comfortable talking about sensitive things (66%), having enough space in communication (62%) and being asked by their GP about personal strains (53%). Higher social support, preference to solve one’s problem without GP help, higher age and better health status predicted more satisfaction with physician–patient communication, while the number of psychosocial problems, gender, years with physician, chronic stress and depression had no influence. According to the Bentler Comparative Fit Index, the pooled structural equation model had a 97.6% better fit than the corresponding model without covariate effects.Higher social support, preference to solve one’s problem without GP help, higher age and better health status but not the number of psychosocial problems predicted more satisfaction with physician–patient communication.Conclusions GPs should be aware of the high occurrence of patients’ psychosocial problems and actively address patients’ social support and self-management preferences which influence patients’ satisfaction with GP communication.Trial registration number The General Practice Care-1 study was registered in the German Clinical Trials Register (DRKS00022330).